Focus on Proficiency (Edinburgh Gate, Halow, 1999)
The book is a complete integrated course for students preparing for the Cambridge Certificat of Proficiency in English examination. It contains clear grammar sections with explanations and practice; study boxes summaring frequiently tested language items; authentic, motivating texts; challenging, real-life communication activities; attractive full colour design; variety of listening extracts, including unscripted recordings; focus on register recognition; full vocabulary review; new interview practice material; and index of structures and functions covered.
Keywords: english language - examinations - study guides,english language - textbooks for foreign speakers,test of english as a foreign language - study guides